EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN SOFTWARE CABRI 3D DITINJAU DARI GAYA BELAJAR SISWA - Putra, Fredi Ganda; Kusmayadi, Tri Atmojo; Sujadi, Imam (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement viewed from the learning style of the students. The learning models compared were the cooperative learning model of the TGT type by using Cabri 3D, the cooperative learning model of the TGT type, and the direct learning model. The type of the research was a quasi-experimental research. Its population was all of the students in grade VIII of State Junior Secondary Schools of Metro City in academic year 2013/2014. The size of the sample was 278 students consisted of 90 in experimental class 1, 95 in experimental class 2, and 93 in control class. The instruments used were mathematics achievement test on the learning material of polyhedron and questionnaire of learning style. The data was analyzed by using two way analysis of variance with unbalanced cells. The conclusions of the research were as follows. (1) The cooperative learning model of the TGT type by using Cabri 3D resulted in a better learning achievement than the cooperative learning model of the TGT type and the direct learning model, the cooperative learning model of the TGT type resulted in a better learning achievement than the direct learning model. (2) The students with the visual learning style had the same learning achievement as those with the kinesthetic learning style, and both of the group had a better learning achievement than those with the auditory learning style. (3) In each category of the learning style, the cooperative learning model of the TGT type by using Cabri 3D resulted in a better learning achievement than the cooperative learning model of the TGT type and the direct learning model, the cooperative learning model of the TGT type resulted in a better learning achievement than the direct learning model. (4) In each of the learning models, the students with the visual learning style had the same learning achievement as those with the kinesthetic learning style, and both of the group had a better learning achievement than those with the auditory learning style.Keywords: TGT , Cabri 3D, Learning Style.